Microbial Succession and Sensory Enhancement in Robusta Wine Coffee Fermentation - Jatmiko, Yoga Dwi; Mulasari, Ratna Agista Putri; Mustamin, Aryan; Puja, Lintang Ratu; Kanita, Anggita Bella Siez (Directorate of Research and Community Services, 2025)
Robusta wine coffee is a fermented product processed through multi-stage anaerobic fermentation to enhance its sensory quality through microbial activity. This study aimed to assess bacterial diversity and succession during fermentation, examine correlations between microbial populations and physicochemical parameters, and evaluate sensory attributes through organoleptic testing. Fermentation was carried out in five stages over 49 days, with bacterial isolation performed on PCA and MRS agar. Isolates were characterized morphologically, followed by Gram staining and API 50 CHL biochemical testing. Physicochemical parameters—pH, temperature, titratable acidity, moisture, and ash—were analyzed at each stage. A total of 26 isolates were recovered, with Simpson diversity index values <1, indicating dominance by certain isolates: A2, A8, A9, B4, D3, D8, and E3. Correlation analysis revealed positive relationships between bacterial counts and both moisture and pH, and negative correlations with temperature, ash, and titratable acidity. Biochemical profiling confirmed several dominant isolates as lactic acid bacteria (LAB): A9 as Lactobacillus fructivorans, B4 as L. delbrueckii, D3 as L. pentosus, D8 as Leuconostoc mesenteroides, and E3 as Lactococcus lactis. Cluster analysis based on phenotypic traits indicated strong similarity among LAB isolates, especially between D3 (L. pentosus) and the reference strain L. plantarum. Organoleptic testing demonstrated that wine coffee was preferred over non-fermented robusta, particularly in terms of aroma, acidity, and aftertaste. These results support the potential use of selected LAB isolates as starter cultures to enhance the sensory consistency and quality of wine coffee products.